Harnessing AI Technologies: Innovations in Literacy Libraries for Diverse Learners - Zalika Icasia Ajwa; Aroha Patel; Anne Moseley (International Institute for Advanced Science & Technology (IIAST), 2024)
Technological advancements have a place in every industry, including libraries. Artificial intelligence (AI) is one technology that libraries may make use of. The authors of this study provide a detailed explanation of how libraries have evolved in the wake of disruption and note many applications of AI that could be applied in library settings. Applications of AI include helping librarians do their jobs more easily and giving users quick, effective service. But the best use of AI necessitates thoughtful thought. Literacy libraries must change to meet the requirements of various learners in this more linked and complicated society. The integration of AI technology is suggested in this article as a creative way to enhance literacy library services for students with various requirements. We investigate the potential of AI in maximizing accessibility, personalizing learning, and early detection of learning issues using conceptual analysis and observational literature. With an emphasis on equity and inclusivity, we also emphasize the opportunities and difficulties associated with implementing AI technology. A responsive, adaptable, and inclusive learning environment can be created for students of different backgrounds and skill levels by using AI into library literacy.